Plant hormones and homeoboxes: bridging the gap? - Hay, A; Craft, J; Tsiantis, M (2004)
Plant hormones are signalling molecules that control growth and development. Growth of the aerial parts of higher plants requires the continuous activity of the shoot apical meristem, a small mound of cells at the apex of a plant. KNOTTED1-like HOMEOBOX (KNOX) genes are involved in regulating meristem activity, however, little is known about how this regulation is mediated. Recent evidence suggests that KNOX transcription factors may control meristem development by regulating the balance of activities of multiple hormones.